2014
DOI: 10.3945/an.113.005116
|View full text |Cite
|
Sign up to set email alerts
|

Come and Get It! A Discussion of Family Mealtime Literature and Factors Affecting Obesity Risk

Abstract: The L.E.A.D. (Locate, Evaluate, and Assemble Evidence to Inform Decisions) framework of the Institute of Medicine guided the assembly of transdisciplinary evidence for this comprehensive, updated review of family meal research, conducted with the goal of informing continued work in this area. More frequent family meals are associated with greater consumption of healthy foods in children, adolescents, and adults. Adolescents and children who consume fewer family meals consume more unhealthy food. School-aged ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
102
3
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 119 publications
(305 reference statements)
3
102
3
14
Order By: Relevance
“…However, associations between higher family meal frequency and lower body mass index (BMI) for youth and their parents have not been consistently found in the literature (Berge et al, 2013; Berge et al, 2015; Berge, Wickel, & Doherty, 2012; Chan & Sobal, 2011; Fulkerson et al, 2014a; Hammons & Fiese, 2011; Martin-Biggers et al, 2014; Sobal & Hanson, 2014). Thus, more research is needed to understand if other aspects of family meals, beyond meal frequency, are important for healthful weight outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, associations between higher family meal frequency and lower body mass index (BMI) for youth and their parents have not been consistently found in the literature (Berge et al, 2013; Berge et al, 2015; Berge, Wickel, & Doherty, 2012; Chan & Sobal, 2011; Fulkerson et al, 2014a; Hammons & Fiese, 2011; Martin-Biggers et al, 2014; Sobal & Hanson, 2014). Thus, more research is needed to understand if other aspects of family meals, beyond meal frequency, are important for healthful weight outcomes.…”
mentioning
confidence: 99%
“…Specifically, recent research has shown family meal frequency measures that include a family dinnertime context component (e.g., sitting and eating with your family rather than just “eat meal together”) are significantly associated with youth BMI outcomes while family meal frequency measures that exclude a context component are not significantly associated with youth BMI outcomes (Horning, Fulkerson, Friend, & Neumark-Sztainer, 2016). Thus, it stands to reason that a positive mealtime context (Berge et al, 2015; Fiese, Foley, & Spagnola, 2006; Fulkerson et al, 2014a; Martin-Biggers et al, 2014; Spagnola & Fiese, 2007), with more consistent family routines and less frequent parent dinnertime media use, provides families more opportunity to engage with one another (e.g., via role modeling or healthful eating mentoring or monitoring), which may be associated with healthier dietary intake and ultimately healthier BMI. If this reasoning is true, the magnitude of the impact of the dinnertime context would depend on the frequency at which meals are occurring.…”
mentioning
confidence: 99%
“…Recently, family meal literature reviews have found robust and positive associations between family meal frequency and beneficial psychosocial outcomes (e.g., positive family relationships 1,2 and reduced risky behaviors 25 ) and dietary quality outcomes (e.g., higher intake of fruits, vegetables and a variety of vitamins/minerals and lower intake of sugar-sweetened beverages (SSB) and energy-dense, nutrient-poor foods 1,37 ) for youth. However, findings have been mixed in regard to associations with youth weight status.…”
mentioning
confidence: 99%
“…Adolescent eating behavior may be strongly influenced by social environments, including friends and family, particularly the parents, who can contribute to the development and maintenance of healthy eating habits [18][19][20]. In addition, family meals can act as a protective factor against nutritional problems that may appear during childhood and adolescence, such as overweight, unhealthy diets, and eating disorders [21].…”
Section: Introductionmentioning
confidence: 99%